2019
DOI: 10.15835/nbha47311499
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Gender Specific CAPS Marker in Turkish Fig (Ficus carica L.) Collection and F1 Progenies

Abstract: In most dioecious plants, distinguishing male and female progenies is not possible until flowering or fruiting stage. The fig (Ficus carica L.) is such a plant where distinguishing male and female plants at the seedling stage can accelerate fig-breeding programs. An orthologue of RAN1 loci was reported to be associated with sex determination in fig (Mori et al., 2017). The objective of this study is to validate this locus on Turkish fig germplasm collection and F1 population obtained from a cross between femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…FcRAN1 was preliminarily speculated to be the sex-determining A gene for figs, and a cleaved amplified polymorphism sequence (CAPS)-based method was established . Ikten and Yilmaz (2019) verified the CAPS method and found that restriction endonuclease PciI provides 100% sex discrimination for PCR products, while restriction endonuclease HpyCH4IV gave some false-positive results. Nevertheless, restriction endonuclease digestion is timeconsuming, the required enzymes are expensive, and wellcontrolled conditions are needed for successful performance.…”
Section: Data Availability Statementmentioning
confidence: 90%
“…FcRAN1 was preliminarily speculated to be the sex-determining A gene for figs, and a cleaved amplified polymorphism sequence (CAPS)-based method was established . Ikten and Yilmaz (2019) verified the CAPS method and found that restriction endonuclease PciI provides 100% sex discrimination for PCR products, while restriction endonuclease HpyCH4IV gave some false-positive results. Nevertheless, restriction endonuclease digestion is timeconsuming, the required enzymes are expensive, and wellcontrolled conditions are needed for successful performance.…”
Section: Data Availability Statementmentioning
confidence: 90%
“…FcRAN1 was preliminarily speculated to be the sex-determining A gene for figs, and a cleaved amplified polymorphism sequence (CAPS)-based method was established ( Mori et al, 2017 ). Ikten and Yilmaz (2019) verified the CAPS method and found that restriction endonuclease Pci I provides 100% sex discrimination for PCR products, while restriction endonuclease Hpy CH4IV gave some false-positive results. Nevertheless, restriction endonuclease digestion is time-consuming, the required enzymes are expensive, and well-controlled conditions are needed for successful performance.…”
Section: Introductionmentioning
confidence: 90%
“…Mori et al (2017) reported that mutational variations of the two SNP regions in RAN1, which is associated with sex determination in figs, caused heterozygous accessions in the 18 male fig accessions. In the current study, five accessions previously reported to be female (Ikten and Yilmaz, 2019) were identified as male based on RAN1associated cleaved amplified polymorphic sequences (CAPS) marker screenings. These heterozygous genome variations may be another reason for the fact that 5 of the 45 caprifigs accessions were found in different RPPs.…”
Section: Unique Synonymous-clonal Structure and Sex Distribution Of Anatolian Figsmentioning
confidence: 99%